Pengaruh Pemberian Zat Pengatur Tumbuh Atonik Dan Media Tanam Terhadap Pembibitan Tanaman Aren Genjah (Arenga pinnata, Merr) - Yanti Ratna Sari; Tutik Nugrahini; Mahdalena Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2017)
The Influence of Atonic Growth Substance and Planting Media Against Aruh Genjah Plant Breeding (Arenga pinnata, Merr). This study aims to determine the effect of proper growth regulator concentration and the best planting medium for the growth of palm seedlings, as well as the effect of interaction between ZPT Atonik and planting media. This research was conducted in Sangatta Lama area of Sangatta Utara Sub-district, East Kutai Regency, with time for 5 (five) months from February to June 2016. The research design used Factorial Randomized Block Design (RAK) 4 x 4 with 3 repetition . The first factor was the administration of Atonic ZPT consisting of 4 levels: z0: without treatment, z1: Atonic ZPT 0.5 ml / 1 liter water, z2: ZPT Atonik 1 ml / 1 liter water, z3: ZPT Atonic 1.5 ml / 1 liter of water. The second factor is the comparison of planting medium consisting of 4 levels: m0: top soil, m1: top soil + sand + manure (1: 1: 1), m2: top soil + husk husk + manure (1: 1: 1 ), m3: top soil + charcoal husk + sand + manure (1: 1: 1: 1). Fingerprint analysis showed that the best effect of ZPT Atonik (Z) on the parameters of plant height was on the first month that is in the treatment of z2 (Atonic ZPT 1 ml / 1 liter water). The best comparison of planting medium (M) to plant height parameters was at month 2 and month 3 was achieved by treatment of m2 (top soil + husk husk + manure = 1: 1: 1) and m3 treatment (Top soil + + Sand + manure = 1: 1: 1: 1). Furthermore, the best treatment of leaflet parameter of month 1 was achieved by treatment of m1 (top soil + sand + manure = 1: 1: 1). The interaction of ZPT Atonik (zxm) comparison and the best planting medium to the leaf number parameter is the 1st month achieved by the z3p1 treatment (Atonic ZPT 1.5 ml / 1 liter water and top soil + sand + manure = 1: 1: 1) . Keywords: Growing Regulators, Planting Media and Aren GenjahThe Influence of Atonic Growth Substance and Planting Media Against Aruh Genjah Plant Breeding (Arenga pinnata, Merr). This study aims to determine the effect of proper growth regulator concentration and the best planting medium for the growth of palm seedlings, as well as the effect of interaction between ZPT Atonik and planting media. This research was conducted in Sangatta Lama area of Sangatta Utara Sub-district, East Kutai Regency, with time for 5 (five) months from February to June 2016. The research design used Factorial Randomized Block Design (RAK) 4 x 4 with 3 repetition . The first factor was the administration of Atonic ZPT consisting of 4 levels: z0: without treatment, z1: Atonic ZPT 0.5 ml / 1 liter water, z2: ZPT Atonik 1 ml / 1 liter water, z3: ZPT Atonic 1.5 ml / 1 liter of water. The second factor is the comparison of planting medium consisting of 4 levels: m0: top soil, m1: top soil + sand + manure (1: 1: 1), m2: top soil + husk husk + manure (1: 1: 1 ), m3: top soil + charcoal husk + sand + manure (1: 1: 1: 1). Fingerprint analysis showed that the best effect of ZPT Atonik (Z) on the parameters of plant height was on the first month that is in the treatment of z2 (Atonic ZPT 1 ml / 1 liter water). The best comparison of planting medium (M) to plant height parameters was at month 2 and month 3 was achieved by treatment of m2 (top soil + husk husk + manure = 1: 1: 1) and m3 treatment (Top soil + + Sand + manure = 1: 1: 1: 1). Furthermore, the best treatment of leaflet parameter of month 1 was achieved by treatment of m1 (top soil + sand + manure = 1: 1: 1). The interaction of ZPT Atonik (zxm) comparison and the best planting medium to the leaf number parameter is the 1st month achieved by the z3p1 treatment (Atonic ZPT 1.5 ml / 1 liter water and top soil + sand + manure = 1: 1: 1) . Keywords: Growing Regulators, Planting Media and Aren Genjah